2022
DOI: 10.1155/2022/2737719
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Mortality in Children: A Referral Center Experience from Iran (Mofid Children’s Hospital, Tehran, Iran)

Abstract: Background. The novel coronavirus disease 2019 (COVID-19) started in Wuhan, China, in December 2019. It spread widely around the world and was described as a pandemic by the World Health Organization (WHO). The knowledge regarding the mortality rate and risk factors of COVID-19 among the pediatric population is lacking. In this regard, we aimed to report the clinical and laboratory characteristics of deceased pediatric patients with SARS-CoV-2 infection. Method. This cross-sectional study was conducted in Mofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 41 publications
8
11
0
Order By: Relevance
“…These differences in ethnic groups may be indicative of wider disparities such as socioeconomic status, cultural differences, or access to healthcare, which are worthy of further study [ 41 ]. Our results are also in line with a recent systematic review up to May 2021, which also found higher odds of severe disease and death in CYP aged >10 years and underlying comorbidities, especially neurological or cardiac conditions [ 42 ], which is consistent with other published studies [ 11 , 15 , 42 , 43 ]. Notably, however, compared to children who died of other causes in England, previous analyses found that underlying health conditions were not overrepresented in children who died of COVID-19 [ 15 , 44 ], or among survivors and non-survivors in children hospitalised for COVID-19 [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…These differences in ethnic groups may be indicative of wider disparities such as socioeconomic status, cultural differences, or access to healthcare, which are worthy of further study [ 41 ]. Our results are also in line with a recent systematic review up to May 2021, which also found higher odds of severe disease and death in CYP aged >10 years and underlying comorbidities, especially neurological or cardiac conditions [ 42 ], which is consistent with other published studies [ 11 , 15 , 42 , 43 ]. Notably, however, compared to children who died of other causes in England, previous analyses found that underlying health conditions were not overrepresented in children who died of COVID-19 [ 15 , 44 ], or among survivors and non-survivors in children hospitalised for COVID-19 [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, these patients had an increased risk of in-hospital mortality than the other patients. These findings were consistent with the results of the previously conducted studies [ 17 , 18 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Pre-existing disorders were observed among 10.2% of the hospitalized children. This finding was consistent with the results of the previous study conducted in Iran [ 17 ]; however, it was much lower than the reported findings by Armin et al [ 18 ]. Comorbidities were a decisive risk factor for ICU admission and COVID-19 mortality.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Age groups were determined based on the World Health Organization Guideline on “COVID-19 disease in children and adolescents.” 12 The clinical severity was determined using the classification system proposed by Dong et al and summarized in Table 1 . 13 14 15 16 17 The medical records of parents and siblings were investigated and the source of infection was determined as a household contact if the SARS-CoV-2 RT-qPCR test of a household contact was positive within 5 days' of the case.…”
Section: Methodsmentioning
confidence: 99%